PENYULUHAN GIZI SEIMBANG UNTUK ANAK SEKOLAH DASAR DI SDN 67 TANGKERANG SELATAN PEKANBARU: Penyuluhan Gizi Seimbang Untuk Anak Sekolah Dasar Di SDN 67 Tangkerang Selatan Pekanbaru - Desfita, Sri; Helsya Anggraini, Fatharani; Yolanda, Helena; Nanda Putri, Melysa; Zulriyanti, Nurfebi (STIKes Hang Tuah Pekanbaru, 2023)
Balanced nutritional consumption needs to be applied every day by school children to meet the body's needs for growth, increased physical activity, and cognitive abilities. Counseling about balanced nutrition at SDN 67 Pekanbaru City using the lecture method is one of the efforts to increase student knowledge so that students have a healthy eating patterns. The pre-test and post-test were carried out orally to determine the increase in students' knowledge about balanced nutrition. The results of this community service showed an increase in students’ knowledge about balanced nutrition, the need for macro and micronutrients for school children, and the arrangements for providing food for school children. Good knowledge of nutrition is needed to establish good behavior or eating habits in school-age children. Keywords: School Age Children, Balanced Nutrition, Counseling Abstrak Konsumsi gizi seimbang perlu diterapkan setiap hari oleh anak sekolah untuk memenuhikebutuhan tubuh akan pertumbuhan, meningkatnya aktivitas fisik, dan kemampuankognitif. Penyuluhan tentang gizi seimbang di SDN 67 Kota Pekanbaru dengan metodeceramah merupakan salah satu upaya untuk meningkatkan pengetahuan siswa sehinggasiswa memiliki pola makan yang sehat. Pre-test dan post-test dilakukan secara lisan untukmengetahui peningkatan pengetahuan siswa tentang gizi seimbang. Hasil kegiatanpengabdian ini menunjukkan adanya peningkatan pengetahuan siswa mengenai giziseimbang, kebutuhan zat gizi makro dan mikro untuk anak sekolah dan pengaturanpemberian makanan untuk anak sekolah. Pengetahuan yang baik tentang gizi diperlukanuntuk membentuk perilaku atau kebiasaan makan yang baik pada anak usia sekolah.Kata Kunci: Anak Usia Sekolah, Gizi Seimbang, Penyuluhan